REDESIGN KANTOR PT. IKAPHARMINDO PUTRAMAS TBK. DENGAN PENDEKATAN PSIKOLOGI RUANG - Salsabilla Wibowo, Khevia; Sheha Gunawan, Ahmad Nur; Bayu, Aditya (Telkom University, 2024)
PT. Ikapharmindo Putramas Tbk. is a multinational pharmaceutical company.This research discusses the redesign of the PT office. Ikapharmindo Putramas Tbk. with a space psychology approach to increase employee dedication, creativity, productivity andwell-being. The problems found in this research were related to the work environment, such as inadequate lighting, disorganized layout, monotonous work space atmosphere,and disorganized storage of goods. This research aims to design the layout of the space to be more organized, reduce employee stress through variations in color and shape, improvelighting according to standards, and provide special furniture for storage. The datacollection method used is qualitative including interviews, observation, documentationand secondary data analysis. It is hoped that the results of this redesign can create a work environment that can support employee welfare, make employees more productive, andprovide a reference for companies in maximizing workspace interior design. Keywords: office, PT. Ikapharmindo Putramas Tbk., space psychology.